Analysis of Donor Motivations in Living Donor Liver Transplantation - Abdeldayem, Hesham; Kashkoush, Samy; Hegab, Bassem Soliman; Aziz, Amr; Shoreem, Hany; Saleh, Shereef (Frontiers in Surgery, 2014)
Objectives: The introduction of the living donor liver transplantation (LDLT) in Egypt as in elsewhere, has raised important psychological conflicts and ethical questions. The objective of this study was to get better understanding of the potential donors’ motives towards LDLT. Methods: This study was conducted on consecutive 193 living –liver donors who underwent partial hepatectomy as donors for LDLT during the period between April 2003 and January 2013, at the National Liver Institute Menoufeyia University, Egypt. Potential donors were thoroughly evaluated preoperatively through a screening questionnaire and interviews as regard their demographic data, relationship to the potential recipient and motives towards proceeding to surgery. They were assured that the information shared between them and the transplant centre is confidential. Results. The donors’ mean age was 25.53± 6.39 years with a range of 18-45 years. Males represented 64.7 % and females were 35.3%. The most common donors (32.1%, n_62,) were sons and daughters to their parents (sons: n_43, daughters: n_19) while parents to their offsprings represent 15% (mothers: n_21, fathers: n_8). Brothers and sisters represent 16.5 % (brothers: n_22, sisters: n_10). Nephews & nieces giving their uncles or aunts were 14%. The number of wives donating to their husbands was 11 (5.7%). Interestingly, there was no single husband who donated his wife. Among the remaining donors, there were 11 cousins & one uncle. Unrelated donors were 20 (10.4%). Several factors seemed to contribute to motivation for donation: the seriousness of the potential recipient condition, the relationship and personal history of the donor to the potential recipient, the religious beliefs, the trust in the health care system, and family dynamics and obligations. Conclusions. Absolute absence of coercion on the living-liver donor’s motives may not be realistic because of the serious condition of the potential recipient. It is mandatory that